Cataclasis and silt smear on normal faults in weakly lithified turbidites. (December 2018) - Nicol, A.; Childs, C.
Abstract: Fault-seal analysis in sand-shale multilayers emphasises the role of shale smear without explicitly accounting for cataclasis. These processes produce low-permeability fault rock and are examined here for small displacement (0.001–70 m) normal faults displacing weakly lithified turbidites comprising ∼55–80% lithic grains. Late Miocene Mount Messenger Formation (MMF) turbidites from the North Island of New Zealand provide fault rock data over a range of scales from individual grains (∼0.1–350 μm) to the height of coastal cliffs (∼10–20 m). Fault rock and unfaulted source beds has been analysed using thin sections, SEM images, particle-size distribution (PSD) measurements and outcrops of faults mainly in cross section. Cataclasis associated with particle size and macroscopic porosity reduction of protolith sandstones commences at low fault shear strains (<1) and continues as fault displacement accrues. The relationship between particle-size reduction and displacement is non-linear with initial rapid cataclasis facilitated by disaggregation of weak lithic and altered feldspar grains along pre-existing grain defects (e.g., grain boundaries, fractures and altered cleavage planes). Silt smear, by contrast, is not accompanied by significant particle-size reduction and appears to have been achieved by intergrain slip and micro-faulting. Despite the occurrence of silt smear, cataclasis can produce a significant proportion (>50%) of the total fault-rock in sand-silt multilayers. The resulting fault-rock thickness varies by up to three orders of magnitude for a given fault displacement and at short distances (2–10 m) along individual faults. Variations in fault-rock thickness and associated cataclasis have the potential to modify the hydraulic properties of faults and may need to be accounted for in fault-seal analysis. Highlights: Fault rock is produced by a combination of sandstone cataclasis and shale smear. Cataclasis is initially rapid, continues with increasing displacement and accounts for more than 50% of fault rock. Shale smear occurs without significant particle-size reduction via intergrain slip and micro-faulting. Cataclasis has the potential to modify the hydraulic properties of faults and may need to be accounted for in fluid-flow models.